2007
DOI: 10.1183/09031936.00035706
|View full text |Cite
|
Sign up to set email alerts
|

Road tunnel air pollution induces bronchoalveolar inflammation in healthy subjects

Abstract: Traffic-related air pollution is associated with adverse respiratory effects. The aim of the present study was to investigate whether exposure to air pollution in a road tunnel causes airway inflammatory and blood coagulation responses.A total of 16 healthy subjects underwent bronchoscopy with bronchial mucosal biopsies and bronchoalveolar lavage (BAL) on two occasions, in random order: once at 14 h after a 2-h exposure to air pollution in a busy road tunnel, and once after a control day with subjects exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 23 publications
(52 reference statements)
2
51
1
Order By: Relevance
“…Particle exposure measured as PM10 has, however, been found to be high in the subway environment. In Stockholm (Sweden), the PM levels in the subway are 5-10 times higher than at street level in the inner city area [8] and comparable to those found in the road tunnel [9]. This is also the case in several other cities such as London (UK) [10,11], Rome (Italy) [12], New York (NY, USA) [13] and Seoul (Republic of Korea) [14].…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Particle exposure measured as PM10 has, however, been found to be high in the subway environment. In Stockholm (Sweden), the PM levels in the subway are 5-10 times higher than at street level in the inner city area [8] and comparable to those found in the road tunnel [9]. This is also the case in several other cities such as London (UK) [10,11], Rome (Italy) [12], New York (NY, USA) [13] and Seoul (Republic of Korea) [14].…”
mentioning
confidence: 53%
“…In an earlier in vivo study performed in a road tunnel, we demonstrated that particles derived from motor traffic induce inflammatory reactions in the lower airways of healthy individuals, such as increased concentration of inflammatory cells in BAL fluid (BALF) [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…have shown chronic diesel exhaust particle exposure in mice to lead to increased CD8 T cells within the lung together with alveolar airspace enlargement 44. Controlled human exposure to diesel exhaust and also exposure to traffic‐related air pollution have both shown increased numbers of lymphocytes within the lungs after pollution exposure 29, 45. Indeed we have found that controlled human exposure to diesel exhaust results in increase in cellular GRZMA mRNA expression in lower respiratory tract leucocytes, with immunocytochemistry indicating an increase in Granzyme A‐positive lymphocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Personal exposures to PM 2.5 , black carbon, and particle number were all elevated during the trip, and were associated with increased exhaled NO levels, which were interpreted as indicators of airway inflammation. Larsson et al (2007) exposed 16 healthy adults to air pollution in a busy road tunnel (B120,000 vpd) with high levels of PM and NO 2 and noted an inflammatory airway response.…”
Section: Exposure Measurements and Distributionsmentioning
confidence: 99%